2022
DOI: 10.1097/cji.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced Myasthenia Gravis: Literature Review of Ocular Manifestations and a Refractory Case

Abstract: Immune checkpoint inhibition is a new and promising therapy approved for the treatment of various malignancies. Pembrolizumab is a potent tumor suppressor that acts by upregulating the immune system to recognize cancer cells which may result in disrupted self-tolerance. We describe a case and perform a literature review of myasthenia gravis with ocular manifestations after treatment with pembrolizumab. Our case had bilateral ptosis refractory to conventional treatment, and she remained functionally blind as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Although appropriate management, including corticosteroids, intravenous immunoglobulin, and plasmapheresis based on mechanical ventilation, yields a favorable prognosis, MG can still be life-threatening. One study on pembrolizumab reported a 30% mortality rate in patients who developed MG, and less than half of the patients achieved full symptom remission [ 7 ]. In that study, only 32% of patients with MG tested positive for AChR antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Although appropriate management, including corticosteroids, intravenous immunoglobulin, and plasmapheresis based on mechanical ventilation, yields a favorable prognosis, MG can still be life-threatening. One study on pembrolizumab reported a 30% mortality rate in patients who developed MG, and less than half of the patients achieved full symptom remission [ 7 ]. In that study, only 32% of patients with MG tested positive for AChR antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…They can have severe clinical presentations, rapid clinical deterioration with long-term sequela and high mortality rates. 5 Some patients present with a triad of MG, myositis and myocarditis and seem to develop respiratory failure more frequently than those with MG alone. Most of the death from MG complications was seen in those with elevated CK levels with MG overlapping with myositis and myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-acetylcholine receptor antibodies were the most commonly found antibodies followed by anti-MuSK and anti-striated muscle antibodies in patients with overlapping MG, myocarditis and myositis. 5 However, no cases have been reported regarding the type of myositis antibodies seen in pembrolizumab-induced myositis or the triad of MG, myositis, and myocarditis. We report positive anti-SSA antibody for the first time in a patient with this triad.…”
Section: Discussionmentioning
confidence: 99%
“…Recent knowledge of ICI-induced MG has been gained from case reports and retrospective case series as prospective trials are missing [16]. The incidence of ICI-MG is estimated to be between 0.2 and 5.0% [17]. The rate of anti-AChR positivity in pure irMG is not definitely established.…”
Section: Immune Checkpoint Inhibitor-induced Myasthenia Gravis and My...mentioning
confidence: 99%
“…For the definite diagnosis or irMG anti-AChR (or anti-MuSK) antibody positivity and pathological electrodiagnostic studies are required [5]. As the incidence of pathognomonic antibodies can be lower than in classic MG, probable irMG can be also diagnosed after improvement with cholinesterase inhibitors [17]. It is clinically important that patients are evaluated for overlapping irMyositis and cardiomyositis.…”
Section: Immune Checkpoint Inhibitor-induced Myasthenia Gravis and My...mentioning
confidence: 99%